2017
DOI: 10.1007/s00484-017-1409-y
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth response of Fokienia hodginsii to recent climate warming and drought in southwest China

Abstract: To date, few attempts have been made to assess the influence of climate change on forest ecosystems and on the relationship between tree growth and climate in humid areas of low latitudes. In this paper, we studied the response of tree growth and forest ecosystem to climate change by using Fokienia hodginsii tree-ring cores from the northern Yunnan-Guizhou Plateau, southwest of China. Tree growth correlates the highest (r = -0.64, p < 0.01) with mean temperature (July-September), but the coefficients were chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Increasing growth sensitivity to spring season moisture availability or drought conditions is becoming predominant during recent years for the Abies spectabilis and other conifer species in the central and western Himalaya, along with weakening responses to growing season temperatures [59][60][61]. Radial growth of Fokienia hodginsii in southwest China shows increasing responses to summer temperature (negative) and precipitation (positive) under a warming and drying climate [62]. Rahman et al (2018) [18] reported that radial growth of Chukrasia tabularis in the lowland forests in Bangladesh showed increased sensitivity to early growing season temperatures and atmospheric water demand in recent decades, probably due to a significant warming trend and an increasing dry season length.…”
Section: Temporal Shift Of Growth-climate Sensitivitymentioning
confidence: 99%
“…Increasing growth sensitivity to spring season moisture availability or drought conditions is becoming predominant during recent years for the Abies spectabilis and other conifer species in the central and western Himalaya, along with weakening responses to growing season temperatures [59][60][61]. Radial growth of Fokienia hodginsii in southwest China shows increasing responses to summer temperature (negative) and precipitation (positive) under a warming and drying climate [62]. Rahman et al (2018) [18] reported that radial growth of Chukrasia tabularis in the lowland forests in Bangladesh showed increased sensitivity to early growing season temperatures and atmospheric water demand in recent decades, probably due to a significant warming trend and an increasing dry season length.…”
Section: Temporal Shift Of Growth-climate Sensitivitymentioning
confidence: 99%
“…Drought-induced tree decline and mortality is increasing in many parts of the world, which could fundamentally alter the composition [35], structure [9], and biogeography [36] of forests. Recently, mature trees of the endangered species F. hodginsii from a natural forest in YGP in southwest China are undergoing large mortality events [12,26]. F. hodginsii growing in its range boundary is a good example of an endangered tree species that may be more vulnerable to drought.…”
Section: Discussionmentioning
confidence: 99%
“…Our tree-ring data was collected from living and dead trees (Table 1), sampled in November of 2014 and 2016 [12], at 1200-1270 m altitude range within the Xi Shui National Nature Reserve (Figure 1). Dead trees were collected in a precipitous slope in Wangxiantai (SCH01), a scenic area.…”
Section: Core Sampling and Analysismentioning
confidence: 99%
See 2 more Smart Citations